Implementasi Sertifikasi Halal, Antara Prinsip Kehati-Hatian Dan Kemudahan - Suparman; Ahmad Afandi; Fathan Fihrisi; Masykur Abdillah (Journal of Contemporary Indonesian Islam, 2026)
This study examines the implementation of halal certification in Indonesia from the perspective of balancing the principles of prudence (ihtiyath) and ease (taysir). Using a literature review approach and a comparative analysis with Malaysia, the study finds that halal certification serves as an important instrument for ensuring consumer protection, legal certainty, and the integrity of halal products. However, overly complex certification procedures may create obstacles for business actors, particularly micro, small, and medium enterprises (MSMEs). To address this challenge, the Indonesian government has introduced various policy reforms, including self-declaration schemes, free halal certification programs, and exemptions for certain products and materials. The study concludes that an effective halal certification system requires a balance between rigorous halal assurance and administrative simplification to support both consumer protection and the development of the halal industry.